Philosophical Insights: Unraveling the Rich Tapestry of Qur'anic Interpretations through Falsafi Tafsir - Sulastri, Ayu; Imadudin, Imadudin (Jurnal Iman dan Spiritualitas, 2024)
The existence of the philosophical interpretation (tafsir falsafi) has sparked serious debates among scholars, who consider it too radical and potentially harmful to the community due to its freedom in utilizing reason. However, through this research, we explore that the diversity in interpreting the Quran is actually a result of human thought, especially in the realm of philosophy, as the quest for meaning in the Quran fundamentally involves philosophical thinking. The objective of this research is to refute views that label philosophical interpretation as a radical and dangerous approach merely because it is associated with the philosophy of that time, especially that which originated from historically non-Islamic Greek philosophy. The research methodology employed is a literature study (library research), involving the collection and screening of data from various sources to be presented systematically. With this argumentation, we aim to prove that philosophical interpretation significantly contributes to enriching the understanding of the Quran. The philosophy that dominates in this interpretation is not something deviant or perilous in interpreting the verses of the Quran but rather a reflection of philosophical thought applied to the object of justification, namely the Quran itself, and not the other way around. The diversity in philosophical approaches contributes significantly to the development of philosophical thought related to the Quran.